The challenge in determining difficulty of laparoscopic liver resection: are we there yet? - Lee, Ser Yee; Chiow, Kah Heng; Goh, Brian Kim-Poh; Chan, Chung Yip (Laparoscopic Surgery, 2018)
Laparoscopic liver resection (LLR) has evolved and improved over the years with a corresponding expansion of its indications. In 2014, after the 2nd International Consensus Conference on LLR in Morioka, Japan, it was concluded that LLR can be the standard of care for minor resections and is in the exploration phase for major resections. With increasing evidence supporting its safety and benefits, along with the expansion of accepted indications, the popularity of LLR has grown with an exponential increase in the number of surgeons adopting LLR worldwide (1-6).